The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12903-022-02490-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the addition of cone-beam CT to panoral imaging reduce inferior dental nerve injuries resulting from third molar surgery? A systematic review

Abstract: Objective This systematic review aims to examine whether cone-beam CT (CBCT) assessment influences the incidence of nerve injury following high-risk mandibular third molar (MTM) surgery. Study Design Randomised controlled trials comparing two and three-dimensional imaging for assessing high-risk MTMs were included. MEDLINE, EMBASE, CENTRAL and the Dentistry and Oral Science Source (DOSS) were systematically searched along with extensive grey litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The information gleaned from such assessments plays a pivotal role in treatment planning, aiding oral and maxillofacial surgeons in making informed decisions regarding the approach to extraction procedures (6). It allows for the identification of potential risk factors, guiding clinicians in determining the optimal technique, such as odontectomy methods, and the need for additional precautions to minimize the likelihood of nerve injuries (7).…”
Section: Introductionmentioning
confidence: 99%
“…The information gleaned from such assessments plays a pivotal role in treatment planning, aiding oral and maxillofacial surgeons in making informed decisions regarding the approach to extraction procedures (6). It allows for the identification of potential risk factors, guiding clinicians in determining the optimal technique, such as odontectomy methods, and the need for additional precautions to minimize the likelihood of nerve injuries (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, however, have found that pre-surgical use of CBCT in cases of surgical removal of the M3 has little to no effect on decision making and, at best, only marginally modifies treatment strategy (Araujo et al, 2019;Aravindaksha et al, 2015;Baqain et al, 2020;. Occasionally, post-operative complications such as permanent sensory disturbances are just as frequent when CBCT is used pre-surgically, compared with panoramic imaging (Clé-Ovejero et al, 2017;Ghaeminia et al, 2015;Klatt et al, 2021;Korkmaz et al, 2017;Robbins et al, 2022).…”
Section: Cbct In Mandibular Third Molar Imagingmentioning
confidence: 99%
“…A large body of literature, however, has found that postoperative complications -including sensory disturbances -do not decrease when CBCT is used compared to panoramic imaging. Surgery time, number of analgesics, and resources used post-surgically are other items that do not decrease with CBCT usage (Clé-Ovejero et al, 2017;Klatt et al, 2021;Robbins et al, 2022). Thus, clinicians should carefully evaluate the necessity of a supplemental CBCT scan.…”
Section: Use and Qualities Of Imaging Modalitiesmentioning
confidence: 99%